Micro-explosion of droplets containing liquids with different viscosity, interfacial and surface tension; Chemical Engineering Research and Design; Vol. 158 - Antonov D. V. Dmitry Vladimirovich; Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Fedorenko R. M. Roman Mikhaylovich (2020, 2020)
Title screen